Effect of dietary patterns on oxidative stress in Patiants with metabolic syndrome: Tehran Lipid and Glucose Study - Parvin Mirmiran; Hoda Hadavi; Azadeh Mottaghi; Fereidoun Azizi (Babol University of Medical Sciences, 2018)
Background: Metabolic syndrome is a prevalent condition with dramatic rising trend worldwide. Single dietary factors, such as omega-3 fatty acids consumption protect body against oxidative damage by reinforcement of dietary total antioxidant capacity but the combination of all dietary components may be more effective when studied as integrated dietary patterns. This present study was designed to assess the association between different dietary patterns and oxidative stress in a population of Tehranian adults suffering from metabolic syndrome. Methods: Dietary data were collected using a validated 147-item semi-quantitative FFQ with a standard serving size. Factor analysis method was used to derive dietary patterns. Blood analysis and anthropometric measurements were also obtained. Oxidative stress was assesses using serum levels of Malondialdehyde (MDA) and total antioxidant capacity (TAC). Results: The regression coefficient for TAC and MDA with different quintiles of dietary patterns, adjusted for potential confounder in model 3 reveal a significant positive association between healthy pattern and serum TAC levels (β=0.244, p=0.008) and also between serum MDA levels and the unhealthy pattern (β=0.387, p=0.0001). On the other hand, a significant negative association found between serum TAC levels (β=-0.289, p=0.001) and the unhealthy pattern, a relationship also noted between serum MDA levels and the healthy dietary pattern (β=-0.273, p=0.002). Conclusions: Our findings suggest that following a healthy pattern filled with fruits and vegetables ameliorates oxidative stress status and on the contrary, attachment to an unhealthy pattern, characterized by higher intakes of fast foods and processed foods, aggravated the oxidative stress levels in Tehranian individuals suffering from metabolic syndrome.